Reciprocal associations between parenting challenges and parents' personality development in young and middle adulthood - Hutteman, Roos (Array, 2014)
Having children affects many aspects of people’s lives. However, it remains unclear to what degree the challenges that come along with having children are associated with parents’ personality development. We addressed this question in two studies by investigating the relationship between parenting challenges and personality development in mothers of new-borns (Study 1, N = 556) and the reciprocal associations between (mastering) parenting challenges and personality development in parents of adolescents (Study 2, N = 548 mothers and 460 fathers). In Study 1, we found the stress of having a new-born baby to be associated with declines in maternal Agreeableness, Conscientiousness, and Emotional Stability. Parenting challenges were also related to personality development in parents of adolescent children in Study 2, with parent-child conflict being reciprocally associated with decreases in Conscientiousness, and Emotional Stability. Mastering parenting challenges in the form of high parenting self-efficacy, on the other hand, was found to be associated with increases in Agreeableness, Conscientiousness, and Emotional Stability, and vice versa. In sum, our results suggest that mastering the challenges associated with the social role of parenthood is one of the mechanisms underlying personality development in young and middle adulthood.